How Employee Engagement and Perceived Organizational Support Drive Innovation Performance - Adebowale I. O.; Khairul Nur Adli (Westscience Press, 2026)
This study examines the effect of employee engagement and perceived organizational support on innovation performance in the Indonesian context. Grounded in organizational behavior and human resource management perspectives, this research employs a quantitative approach using survey data collected from 175 respondents across various sectors. Data were gathered באמצעות a structured questionnaire measured on a Likert scale and analyzed using SPSS Statistics 25. The analysis includes descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression. The results reveal that employee engagement has a significant positive effect on innovation performance, indicating that employees who are more emotionally and cognitively involved in their work tend to contribute more actively to innovative activities. Perceived organizational support also shows a significant positive influence, suggesting that supportive organizational environments encourage employees to generate and implement new ideas. Furthermore, the simultaneous analysis demonstrates that both variables collectively contribute significantly to innovation performance, with a coefficient of determination (R²) of 0.507. These findings highlight the importance of strengthening employee engagement and organizational support as strategic drivers of innovation. The study contributes to the literature by providing empirical evidence from Indonesia and offers practical implications for organizations aiming to enhance innovation through effective human resource management practices.